Review of Greenhouse Gas Emissions from Rewetted Agricultural Soils - Bianchi, Andrea; Larmola, Tuula; Kekkonen, Hanna; Saarnio, Sanna; Lång, Kristiina (Society of Wetlands Scientists, 2021)
Climate policies encourage the search for greenhouse gas (GHG) mitigation options in all economic sectors and peatland rewetting is one of the most efficient mitigation measures in agriculture and land use. The benefits shown in the national GHG inventories, however, depend not only on the actual mitigation actions on the ground but also how well the effects can be reported. Currently there are no specific emission factors for reporting GHG emissions from rewetted agricultural soils as the current emission factors are aggregated for several pre-rewetting land use types. Also, rewetting can aim at either restoration or different forms of paludiculture which may differ in their GHG profile and thus demand disaggregated emission factors. We compiled the current knowledge on GHG emissions on sites where rewetting has occurred on former agricultural peatland in temperate or boreal climate zones. The recent data suggest that on average the current emission factors for rewetting nutrient-rich sites published by the Intergovernmental Panel for Climate Change (IPCC) provide a good estimate for reporting emissions from rewetting in the temperate zone. However, the total GHG balances differed widely in restoration, Sphagnum farming and production of emergent plants in paludiculture and it is evident that disaggregated emission factors will be needed to improve the accuracy of reporting the effects of mitigation measures in the GHG inventories.
Keywords: Peatland; Climate; GHG; Rewetting; Paludiculture; Emission factor